QoS Management in WSN-MCN Convergence Network Using Priority Based Traffic Models - Anita Swain; Arun Kumar Ray (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Technological advancements and increased developments leads to increase the development of hand-held devices which encourage the growth of Machine-to-Machine (M2M) communication. In this context devices belongs to heterogeneous network require a common platform to meet the challenges of data centric wireless services and applications. To satisfy the needs of M2M communication, Mobile Cellular Network (MCN) and Wireless Sensor Network (WSN) converged to a single platform. In this paper two priority models has been proposed with non preemptive priority and preemptive priority to analyze the data traffic at MAC layer of the converged network. The performance matrices are determined to maintain QoS in terms of reduced dropping and blocking probability, waiting time in the queue etc. Finally, the proposed models are compared in terms of QoS factors.